2020
DOI: 10.1111/1475-6765.12388
|View full text |Cite
|
Sign up to set email alerts
|

Congruence between voters and parties: The role of party‐level issue salience

Abstract: The level of congruence between parties and their voters can vary greatly from one policy issue to another, which raises questions regarding the effectiveness of political representation. We seek to explain variation in party–voter congruence across issues and parties. We focus on the hypotheses that (1) average proximity between the positions of voters and the party they vote for will be highest on the issues that the party emphasises in the election campaign and that (2) this relationship will be stronger fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…. and those with whom they disagree.’ Of most relevance to this study, research also indicates that ideological proximity between voter and party tends to be higher on personally salient issues (Giger and Lefkofridi, 2014) and on issues emphasised by the party during elections (party-level salience) (Costello et al, 2021), with niche parties performing better in both instances. These findings imply that the importance citizens attach to single issues plays a fundamental role in the representational relationship between parties and voters.…”
Section: The Consequences Of Voter–party Incongruence For Affective E...mentioning
confidence: 74%
“…. and those with whom they disagree.’ Of most relevance to this study, research also indicates that ideological proximity between voter and party tends to be higher on personally salient issues (Giger and Lefkofridi, 2014) and on issues emphasised by the party during elections (party-level salience) (Costello et al, 2021), with niche parties performing better in both instances. These findings imply that the importance citizens attach to single issues plays a fundamental role in the representational relationship between parties and voters.…”
Section: The Consequences Of Voter–party Incongruence For Affective E...mentioning
confidence: 74%
“…Moreover, party–voter congruence, i.e., the closeness between party position and voter preference, is the greatest for issues that are particularly salient during the election campaign (Costello et al. 2021 ). This effect is driven by the fact that voters need to know which positions parties take on given issues.…”
Section: The Impact Of the Covid-19 Pandemic On Afd Supportmentioning
confidence: 99%
“…When the ideologically adjacent party on the left–right dimension has a clear position on alternative issues and emphasizes those issues more (Costello et al, 2021), the lack of gains from the economic policy outcomes due to compromise can be substituted with gains from the other issue area. Earlier literature indeed showed that parties with greater issue diversity, in general, tend to cooperate more with other parties, as diversity provides a large space for bargaining and compromise rather than intensifying ideological tensions due to parties' efforts to preserve their distinct positions towards their electorate (Greene, 2017: 580).…”
Section: Non‐economic Issue Salience and Coalition Formationmentioning
confidence: 99%